Examining the relation between emotional experiences and emotional expressions in competitive tennis matches - Fritsch, J.; Fiedler, J.; Hatzigeorgiadis, A.; Jekauc, D. (Frontiers in Psychology, 2023)
Introduction Emotions consist of different components such as the emotional experience, physiological reactions, action tendencies, or emotional expressions. Assessing the relation of these components may help to better understand the role of emotions in sport competitions. Based on the component process model of emotions, the goal of the present study was to assess the relation between emotional experiences and emotional expressions.